(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
This article provides a scientific analysis of the issues related to the legal regulation of the agricultural sector. In particular, it examines the system of legal relations between farms and agricultural clusters, which are considered the main entities of the sector, their rights and obligations, legal status, and liability, as well as the scientific-theoretical views expressed by legal scholars on these matters. Furthermore, the article analyzes the norms of both European Union and national legislation concerning the agricultural sector. Opinions were expressed about the fact that the legal nature and specific features of the relations between farms and clusters have not been researched in the national legal doctrine, the presence of illegal interference by state bodies and other bodies in the activities of these entities, especially the lack of uniform approaches to the legal status of agricultural clusters, the need to create effective legal mechanisms aimed at strengthening the legal protection of farms and guaranteeing the inviolability of their property. Improvement of the civil-legal basis of regulation of relations between agricultural clusters and farms, including the adoption of the Law "On Clusters and Cluster Activities" and in this law, the concept of cluster, the procedures for organizing and implementing its activities, legal status, rights and obligations, property, responsibility, as well as the procedure for the organization of cluster management bodies and the implementation of their activities, the structure of cluster founders and the relations between them are regulated. Conclusions were drawn up on the reorganization and termination of cluster activities